Cartography of Free-Living Amoebae in Soil in Guadeloupe (French West Indies) Using DNA Metabarcoding - Yann Reynaud; Célia Ducat; Antoine Talarmin; Isabel Marcelino (Pathogens, 2020)
Free-living amoebae (FLA) are ubiquitous protists. Pathogenic FLA such as N. fowleri can be found in hot springs in Guadeloupe, soil being the origin of this contamination. Herein, we analyzed the diversity and distribution of FLA in soil using a targeted metataxonomic analysis. Soil samples (n = 107) were collected from 40 sites. DNA was extracted directly from soil samples or from FLA cultivated at different temperatures (30, 37 and 44 °C). Metabarcoding studies were then conducted through FLA 18SrDNA amplicons sequencing; amplicon sequence variants (ASV) were extracted from each sample and taxonomy assigned against SILVA database using QIIME2 and SHAMAN pipelines. Vermamoeba were detected in DNA extracted directly from the soil, but to detect other FLA an amoebal enrichment step was necessary. V. vermiformis was by far the most represented species of FLA, being detected throughout the islands. Although Naegleria were mainly found in Basse-Terre region, N. fowleri was also detected in Grand Terre and Les Saintes Islands. Acanthamoeba were mainly found in areas where temperature is approx. 30 °C. Vannella and Vahlkampfia were randomly found in Guadeloupe islands. FLA detected in Guadeloupe include both pathogenic genera and genera that can putatively harbor microbial pathogens, therefore posing a potential threat to human health.